2011
DOI: 10.1364/boe.2.000696
|View full text |Cite
|
Sign up to set email alerts
|

Wide-field multiphoton imaging of cellular dynamics in thick tissue by temporal focusing and patterned illumination

Abstract: Wide-field temporal focusing is a novel technique that provides optical sectioning for imaging without the need for beam scanning. However, illuminating over large areas greatly reduces the photon density which limits the technique applicability to small regions, precluding functional imaging of cellular networks. Here we present a strategy that combines beam shaping and temporal focusing of amplified pulses (>1 µJ/pulse) for fast imaging of cells from the central nervous system in acute slices. Multiphoton vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 23 publications
0
49
0
Order By: Relevance
“…Integrated with patterned illumination, the system could further be applied for functional excitation [17,28,29,31], 3D fabrication [30], and structured illumination purposes [39][40][41][42]. In this paper, we have demonstrated that the AEC would vary with different patterns at the same single spatial frequency and different orientations, and could reach nearly 29 % difference, e. g., from À11 % to + 18 % with 1.09 mm À1 spatial frequency patterns at the 908 and 08 orientations.…”
Section: Discussionmentioning
confidence: 89%
“…Integrated with patterned illumination, the system could further be applied for functional excitation [17,28,29,31], 3D fabrication [30], and structured illumination purposes [39][40][41][42]. In this paper, we have demonstrated that the AEC would vary with different patterns at the same single spatial frequency and different orientations, and could reach nearly 29 % difference, e. g., from À11 % to + 18 % with 1.09 mm À1 spatial frequency patterns at the 908 and 08 orientations.…”
Section: Discussionmentioning
confidence: 89%
“…Compared to conventional beam scanning multiphoton microscopy, widefield multiphoton microscopy using the temporal focusing technique detects the overall fluorescence and harmonic generation signal of the entire illumination area, which depends on the laser beam spot size and the magnification of the microscope. The advantage of widefield multiphoton microscopy is that less time is required to capture one frame, enabling a fast frame rate for capturing dynamic events [7,8] or fast microfabrication applications [9,10]. With a fast, high-sensitivity camera and an ultrahigh peak power laser, an imaging rate of a few hundred frames per second can be achieved in widefield multiphoton microscopy [11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been successfully implemented to image biological samples [3,4], cellular dynamics [5,6], as well as for microfabrication [7][8][9]. TF2p microscopy is, in essence, simply a 4-f pulse shaper proposed by Froehly, Colombeau, and Vampouille [10] and Martinez, Gordon, and Fork [11] with the exception that there is no second grating to recombine the pulse.…”
Section: Introductionmentioning
confidence: 99%